Different Virus-Derived siRNAs Profiles between Leaves and Fruits in Cucumber Green Mottle Mosaic Virus-Infected Lagenaria siceraria Plants - Li, Junmin; Zheng, Hongying; Zhang, Chenhua; Han, Kelei; Wang, Shu; Peng, Jiejun; Lu, Yuwen; Zhao, Jinping; Xu, Pei; Wu, Xiaohua; Li, Guojing; Chen, Jianping; et al. (Frontiers in Microbiology, 2016)
RNA silencing is an evolutionarily conserved antiviral mechanism, through which virus-derived small interfering RNAs (vsiRNAs) playing roles in host antiviral defence are produced in virus-infected plant. Deep sequencing technology has revolutionized the study on the interaction between virus and plant host through the analysis of vsiRNAs profile. However, comparison of vsiRNA profiles in different tissues from a same host plant has been rarely reported. In this study, the profiles of virus-derived small interfering RNAs (vsiRNAs) from leaves and fruits of Lagenaria siceraria plants infected with Cucumber green mottle mosaic virus (CGMMV) were comprehensively characterized and compared. Many more vsiRNAs were present in infected leaves than in fruits. vsiRNAs from both leaves and fruits were mostly 21- and 22-nt in size as previously described in other virus-infected plants. Interestingly, vsiRNAs were predominantly produced from the viral positive strand RNAs in infected leaves, whereas in infected fruits they were derived equally from the positive and negative strands. Many leaf-specific positive vsiRNAs with lengths of 21-nt (2,058) or 22-nt (3,996) were identified but only six (21-nt) and one (22-nt) positive vsiRNAs were found to be specific to fruits. vsiRNAs hotspots were only present in the 5’-terminal and 3’-terminal of viral positive strand in fruits, while multiple hotspots were identified in leaves. Differences in GC content and 5'-terminal nucleotide of vsiRNAs were also observed in the two organs. To our knowledge, this provides the first high-resolution comparison of vsiRNA profiles between different tissues of the same host plant.